Jurisdiction over development control in the oceas space of island states and archipelagic states with special reference to Trinidad and Tobago. - GOODRIDGE, James Allan (1995)
Reviews the management of ocean space in island states and archipelagic states. Recommends a new approach which would deal with the harmonization of developmental and other activities, as well as with the conflicting and competing users.